The impact of intensive care admission criteria on elderly mortality - Cintra,Marco Túlio Gualberto (2019)
SUMMARY OBJECTIVE To review systematically the influence of admission criteria on the mortality of elderly patients under intensive therapy. METHODS We performed a search on the PUBMED and BIREME databases by using the MeSH and DeCS terms “intensive care units”, “patient admission”, and “aged” in Portuguese, English, and Spanish. Only prospective and retrospective cohort studies were included. We analyzed the severity score, type of hospital admission, quality of life, co-morbidities, functionality, and elderly institutionalization. RESULTS Of the 1,276 articles found, thirteen were selected after evaluation of the inclusion and exclusion criteria. It was observed that the severity score, functionality, and co-morbidities had an impact on mortality. It was not possible to determine which severity score was more suitable. CONCLUSION We suggest that analysis of functionality, co-morbidities, and severity scores should be conducted to estimate the elderly mortality in relation to the admission to intensive care units.